Adapting the workplace to the needs of older people as a challenge for industrial ergonomics - Kowalczyk, Anna; Kulczycka, Kinga; Chodoła, Izabela; Kulina, Dorota (Journal of Education, Health and Sport, 2018)
In Poland, as well as in the European Union as a whole, the percentage of older people is gradually increasing. This translates into an ageing workforce. Due to the lack of generational replacement, older Poles will be forced to continue working longer than their parents or grandparents. Unfortunately, the natural consequence of the aging of the body is a number of changes that make it difficult or even impossible to perform work. Age is one of the factors: reduced mobility and longer response times, reduced aerobic capacity or decreased sensory and sensory abilities. Older people suffer from a deterioration in their general state of health. However, age is one of the few, but not the only, risk factors for inability to work. This means that while it is not possible to deduct metric years, other factors that affect an employee's ability to continue working may be modified. For this reason, ergonomic measures should have an impact on them and reduce their negative effects, thereby affecting the length and quality of working life of older people. The aim of this paper is to analyse the changes in the possibilities of working with age and to present proposals concerning the adjustment of the workplace to older people.